Chlorinated pesticide residues in human breast milk collected from southern Jordan in 2012/2013. (2nd October 2015) - Al Antary, Tawfiq M.; Alawi, Mahmoud A.; Estityah, Hussein; Haddad, Nizar; Al-Antary, Eman T.
Abstract: Chlorinated pesticide residues in human breast milk from five southern Jordan districts were analyzed in 2012/2013. The total number of samples from all districts was 100. The number of samples gathered from each district was collected according to their population densities. The present study shows that 59% of the samples which contained pesticides' residues were p, p' -DDE, 30% contained β-HCH, 10% contained p, p′ -DDT, 6% contained α-HCH, 2% contained heptachlor and 1% contained endrin. These human milk samples were free of aldrin, dieldrin, α-endosulfan, β-endosulfan, HCB, γ-HCH, o, p′ -DDD, o, p′ -DDT and o, p′ -DDE. The levels of the six mentioned compounds detected in all mother's milk samples were higher in Ghor El-Safi district compared with the other four districts. In this study, it is recommended to continue the pesticides residues monitoring in all parts of Jordan, particularly in Ghor El-Safi district and other regions in the cultivated Jordan Valley.